Fitting the Hype Cycle to Sharing Economy Innovations - Julia CUNHA; Anton SENTIC; Stephanie TEUFEL (Communications of International Proceedings, 2020)
Disruptive sharing-economy technologies, unlike other innovations, follow a different version of the Hype Cycle. The traditional graphic model helps to predict the behaviour of collective expectations, supports entrepreneurial decisions and strategic investments. However, when applied to such collaborative solutions, based on the concept of sharing rather than owning, some steps seem to differ. In this paper, interesting findings came from applying a mixed-method approach and from a closer analysis of two innovative and disruptive sharing economy companies: Uber and Airbnb. Foremost, they presented two positive hypes on public expectations rather than one. Consequently, the companies also had to overcome two phases of disappointment. This finding indicates that predictions using the Hype Cycle, when applied to such innovations, may have to be revisited and consider a different pattern.
Keywords: Sharing Economy; Disruptive Technologies; Hype Cycle; Uber And Airbnb.